1995
DOI: 10.1002/arch.940290406
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of two AKH‐related peptides from cicadas

Abstract: Two peptides related to locust adipokinetic hormone and crustacean red pigment concentrating hormone were isolated by high performance liquid chromatography from the cicadas Cacama valavata and Diceroprocta semicincta. Both species have the same peptides. The structure of one of the peptides is pGlu-Val-Asn-Phe-Ser-Pro-Ser-Trp-Gly-Asn-amide. The mass spectrum, amino acid composition, and amino acid sequence of the other peptide suggest that it is almost identical to the first peptide. However, the exact nature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 9 publications
(11 reference statements)
1
10
0
Order By: Relevance
“…However, in the main fraction, the AKH from N. glauca was unequivocally detected by its characteristic sodium and potassium adduct masses in MALDI‐MS studies and its sequence was assigned by ESI MS; comparative retention studies on RP‐HPLC with other AKH peptides confirmed it as being an octapeptide, Anaim‐AKH (primary sequence shown in Table 2), which had previously been isolated from A. imperator (Gäde et al ., 1994). An identical N ‐terminal sequence, but extended at the C ‐terminus by the amino acid residues Gly and Asn, is found in a number of homopteran cicada species and denoted Placa‐HrTH (Table 2) (Gäde & Janssens, 1994; Raina et al ., 1995; Veenstra & Hagedorn, 1995). Although the AKH peptides of P. apterus , denoted Pyrap‐AKH and Peram‐CAH‐II, are also octapeptides, they differ from Anaim‐AKH by three and four amino acid substitutions, respectively (Table 2).…”
Section: Resultssupporting
confidence: 92%
“…However, in the main fraction, the AKH from N. glauca was unequivocally detected by its characteristic sodium and potassium adduct masses in MALDI‐MS studies and its sequence was assigned by ESI MS; comparative retention studies on RP‐HPLC with other AKH peptides confirmed it as being an octapeptide, Anaim‐AKH (primary sequence shown in Table 2), which had previously been isolated from A. imperator (Gäde et al ., 1994). An identical N ‐terminal sequence, but extended at the C ‐terminus by the amino acid residues Gly and Asn, is found in a number of homopteran cicada species and denoted Placa‐HrTH (Table 2) (Gäde & Janssens, 1994; Raina et al ., 1995; Veenstra & Hagedorn, 1995). Although the AKH peptides of P. apterus , denoted Pyrap‐AKH and Peram‐CAH‐II, are also octapeptides, they differ from Anaim‐AKH by three and four amino acid substitutions, respectively (Table 2).…”
Section: Resultssupporting
confidence: 92%
“…Concerning other Hemiptera, the database is very small, with AKHs isolated and sequenced from only two cicadomorphan families, namely the Cicadidae (five species) and Cercopidae (one species). Studies on Cicadidae reveal that five cicada species each contain two decapeptides designated as Placa‐HrTH‐I and II; enigmatically, these peptides are separable by HPLC yet they have the same mass and primary sequence (pEVNFSPSWGN amide); thus, a hither‐to unknown post‐translational modification is suspected (Gäde & Janssens, 1994; Raina et al , 1995; Veenstra & Hagedorn, 1995). In Locris arithmetica (family Cercopidae), the AKHs Peram‐CAH‐I and Pyrap‐AKH are present (Gäde, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This modification is unique because it is not the common O-glycosylation of serine or threonine, or N-glycosylation of asparagine residues, instead the hexose is thought to be linked by C-glycosylation to the C-2 atom of the indole ring of tryptophan (as shown to occur in human ribonuclease [12]). Another, as yet unidentified, modification for an AKH member isolated from the corpora cardiaca of cicadas has also been postulated independently by three research groups [13][14][15].…”
Section: Introductionmentioning
confidence: 88%